1998
DOI: 10.1097/00005537-199811000-00003
|View full text |Cite
|
Sign up to set email alerts
|

Tissue‐conserving surgery for prognosis, treatment, and function preservation

Abstract: This report describes the effectiveness of Mohs' histographic sectioning and selective neck dissection as a means of determining prognostic information that can be used to develop a focused and cost-effective treatment program that, along with contemporary reconstructive techniques, provides a potential enhancement of function preservation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
1

Year Published

2004
2004
2016
2016

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 24 publications
0
9
1
Order By: Relevance
“…Therefore, strengthening the fact that clinical palpation is grossly inadequate for evaluation of N0 neck in oral SCC. [151617] Moreover, USG was not able to pick the metastases in this 33% clinically N0 necks in our study. This is in accordance with the other studies where available radiological investigative tools have shown some improvements in the detection of neck metastases, but sensitivity ranged between 70% and 80%.…”
Section: Discussioncontrasting
confidence: 64%
“…Therefore, strengthening the fact that clinical palpation is grossly inadequate for evaluation of N0 neck in oral SCC. [151617] Moreover, USG was not able to pick the metastases in this 33% clinically N0 necks in our study. This is in accordance with the other studies where available radiological investigative tools have shown some improvements in the detection of neck metastases, but sensitivity ranged between 70% and 80%.…”
Section: Discussioncontrasting
confidence: 64%
“…The great challenge that is being faced by the head and neck oncologists and surgeons is the correct identification of the subset of head and neck cancer patients, of which oral carcinoma constitutes about 30% [90], without micro metastases to the cervical lymph nodes. Clinical palpation of the neck combined with the radiological investigative tools has not been able to correctly identify all these patients [39,102,130]. Despite the increase in knowledge and advancement in cancer management, there is still no method to determine correctly the real micro metastatic disease free neck.…”
Section: Justification Of the Studymentioning
confidence: 99%
“…Some large nodes may be inflammatory while some impalpable nodes may be carcinomatous [32,108]. Clinical palpation of the neck is not adequate for the correct identification of patients with neck node metastasis [39,102,130]. Factors such as neck fat thickness, neck stiffness or contraction, pain and swelling may affect the identification of neck node by palpation.…”
Section: Diagnosing the Node-negative Neckmentioning
confidence: 99%
See 1 more Smart Citation
“…Their result implies that frozen section margins are not worth their cost. However, the authors did not include any indirect costs that would be saved for the four patients who would benefit from the procedure,in terms of work absenteeism or lost productivity due to premature death.In this sense benefits were not comprehensively measured.In a study by Schuller et al [45],the costs for Mohs histographic sectioning to assess margins prior to HNC surgery were determined to be $978 (€1,300) for one layer of tissue, $1,415 (€1,881) for two layers, $1,872 (€2,488) for three layers, and $1,964 (€2,611) for four layers.…”
Section: Surgerymentioning
confidence: 99%